The basics of edible insect rearing : Handbook for the production chain - Claeys, J.; Haenen, O.L.M.; Loon, J.J.A. van; Spranghers, T. (Series of Insects as Food and Feed., 2022)
Looking for a handbook on how to design and upscale edible insect rearing? This easy to read handbook describes the basic knowledge and a detailed step-by-step plan for rearing edible insects. The book presents information essential for further development of the entire insect chain and contains many practical recommendations for the start/setup of professional insect rearing. The reader is first submerged into the fascinating world of edible insects such as black soldier fly, housefly, mealworm, cricket, and locust. A concise overview is provided to get more familiar with the biology and physiology of edible insects. Based on this basic knowledge the book focuses on design principles for large scale insect production, facility design, engineering, insect production management, management of unwanted organisms, economics, and aspects related to the legal framework. The chief editor, co-editors and lead authors of the chapters are from Belgium, Denmark and The Netherlands. These countries have a tradition of professional insect rearing. Reading this handbook will contribute to a successful entrepreneurship in edible insect rearing. This handbook also contains very interesting teaching materials for secondary, higher, and university education.contains very interesting teaching materials for secondary, higher, and university education.